Digital Transformation of Urban Mobility: An Exploration of Para Transit Users' Behavior - Ghulam Habib; Zunair Ahmed; Ammar Yasir; Talha Sabir (Journal Of Social Science (JoSS), 2025)
Digital transformation is revolutionizing urban mobility, particularly in how people use para transit services. These services cater to users who require specialized transportation due to disabilities, medical conditions, or agerelated limitations. Understanding the behavior of para transit users is crucial in optimizing these services to meet their unique needs. Utilizing digital technologies in urban mobility has opened up a world of possibilities for para transit users. From on-demand booking apps to real-time tracking and integrated payment systems, digital transformation has made it easier than ever for users to access and use these services. This has not only improved the convenience and efficiency of para transit but has also enhanced the overall user experience. One of the key aspects of digital transformation in urban mobility is the collection and analysis of data on para transit users' behavior. By tracking users' preferences, habits, and challenges, transportation providers can identify areas for improvement and tailor their services to better meet the needs of their customers. This datadriven approach allows for more personalized and responsive service delivery, ultimately enhancing the quality of life for para transit users. By understanding and addressing the behavior of these users, transportation providers can create more efficient, responsive, and inclusive systems that prioritize the needs and preferences of all individuals. Digital technologies hold immense potential for improving the overall quality and accessibility of para transit services, ultimately enhancing the mobility and independence of users in urban environments.